INDUSTRI LAPIS LISTRIK OLEH KULTUR CAMPURAN MIKROALGA AIR TAWAR TERAMOBILISASI - Mawar DS Silalahi; Astri Rinanti Nugroho; Melati Ferianita Fachrul,; Rositayanti Hadisoebroto; Laras Kurnia (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2017)
Research has conducted as an alternative form of advanced treatment in order to eliminate copper (Cu2+) heavy metal contained in electroplating industrial wastewater. The process is conducted biologically by utilizing the ability of mixed cultures of freshwater microalgae immobilized. The purpose of this study was to determine the removal efficiency for copper (Cu2+) using microalgae single and microalgae cultures mixed, determine the removal efficiency for copper (Cu2+) using mixed cultures microalgae which immobilized by alginate, and determine the influence of temperature and initial concentration of wastewater on the efficiency removal of copper metal (Cu2+) by mixed cultures of the immobilized microalgae. Microalgae are isolated from Setiabudi Reservoir, and purified in order to obtain Ankistrodesmus sp and Chlorella sp. These biosorbents then immobilized by adding alginate to form beads with a diameter of ± 0.5 cm. Artificial biosorbent cultivated in a growth medium Phovasoli Haematococcus Medium (PHM) in a series of batch cultures. The study consisted of three phases, namely the determination of biosorbent mobile and immobilized, optimization of temperature variations (25oC, 30oC and 35oC), and optimization of the initial concentration of wastewater (3 mg/l, 5 mg/l, 10 mg/ l, 15 mg/ l, and 15 mg l) at pH 4 and 120 minutes contact time. These used biosorbent was a single microalgae Ankistrodesmus sp and Chlorella sp and mixed cultures consisting of microalgae Ankistrodesmus sp and Chlorella sp with 1:1 ratio. The results prove that the removal efficiency for copper (Cu2+) by mixed cultures of microalgae was higher than either mobile or single immobilized. Copper (Cu2+) removal efficiency was proof depend on temperature process and the initial concentration of the wastewater. The optimal removal of copper (Cu2+) with immobilized biosorbent occurred at 30 °C with an initial concentration of waste by 17.808 mg /l with a value of 82.54% ± 0.11 for Ankistrodesmus sp; 83.66% ± 0.15 for Chlorella sp; and 86.39% ± 0.34 for a mixed cultures.